The Utilisation of population pharmacokinetic-pharmacodynamic modelling in dosing individualisation: the example of radioactive iodine 131I in the treatment of benign thyroid diseases - Topić Vučenović, Valentina (Archives of Pharmacy, 2022)
In the emerging digital era in health systems, there is a striving to implement modern pharmacometric approaches to dosing individualisation into routine clinical practice with the aim of rational pharmacotherapy and improving patients’ health care. These approaches take into account prior knowledge of the patient-disease-drug system, variability in that system and therapeutic drug or biomarker monitoring data, and an integral term prevailing in literature to describe them is model-informed precision dosing (MIPD). Among other pharmacometric models, MIPD uses population pharmacokinetic-pharmacodynamic models, as they enable identifying and quantifying sources of variability in different populations and subpopulations of patients, which is the basis for individualisation of therapy. Therefore, this paper aims to present the possibilities of applying population models in improving dosing individualisation on the example of the population biokinetic and dynamic model of 131I in the treatment of benign thyroid diseases (1, 2). Since 131I exhibits significant interindividual variability in pharmacokinetics and pharmacodynamics, the application of population models in the individualisation of dosing can significantly contribute to the improvement of the safety and efficacy of the therapy. The development of the MIPD concept applicable in routine clinical practice requires joint efforts of the scientific and professional community, educational institutions and regulatory bodies, given that it is necessary to overcome numerous obstacles of a conceptual and practical nature in order to move from model development to its wide clinical application, including model qualification, as well as the integration of application tools for clinicians into electronic health systems.